A real-world drug safety surveillance study from the FAERS database of hepatocellular carcinoma patients receiving pembrolizumab alone and plus lenvatinib - Huaxiang Wang; Junjun Li; Xiuling Zhu; Ruling Wang; Yunyan Wan (Scientific Reports)
Abstract Pembrolizumab plus Lenvatinib is regarded as a significant treatment option for advanced unresectable hepatocellular carcinoma (HCC). This study aims to meticulously monitor and identify adverse events (AEs) related to this combined therapy, enhance patient safety, and offer evidence-based recommendations for the appropriate use of these drugs. We gathered adverse drug reactions (ADRs)-related data from the FAERS database for HCC patients who received Pembrolizumab, both alone and in combination with Lenvatinib from the first quarter of 2014 to the fourth quarter of 2023. ADRs signal detection was performed using the ROR, PRR, BCPNN, MHRA, and MGPS methods. We gathered data on 459 and 358 AEs from patients with HCC treated with pembrolizumab alone and in combination with lenvatinib, respectively. Using four signal quantification techniques, we identified 50 and 38 distinct AEs, which were classified into 15 different System organ class (SOC) categories. Notably, the most common AEs associated with pembrolizumab were gastrointestinal disorders and hepatobiliary disorders. In both patient groups, the most frequently reported AEs were hepatic encephalopathy, blood bilirubin increased and diarrhea. We also observed some unexpected significant AEs, such as dehydration, skin ulcers, and intestinal perforation. The countries reporting the highest number of AEs were the United States, followed by China, France, and Japan. The median onset time for AEs related to pembrolizumab alone and its combination with lenvatinib was 80.5 days (interquartile range 20.0–217.3 days) and 77.5 days (interquartile range 19.7–212.3 days), respectively. This study offers new insights into the monitoring and management of ADRs in HCC patients receiving pembrolizumab alone or in combination with lenvatinib. It is crucial to closely monitor the safety of this treatment regimen in HCC patients to avoid serious AEs.